Improvement in upper leg muscle strength underlies beneficial effects of exercise therapy in knee osteoarthritis: secondary analysis from a randomised controlled trial. Issue 2 (June 2015) - Knoop, J.; Steultjens, M.P.M.; Roorda, L.D.; Lems, W.F.; van der Esch, M.; Thorstensson, C.A.; Twisk, J.W.R.; Bierma-Zeinstra, S.M.A.; van der Leeden, M.; Dekker, J.
Abstract: Objectives: Although exercise therapy is effective for reducing pain and activity limitations in patients with knee osteoarthritis (OA), the underlying mechanisms are unclear. This study aimed to evaluate if improvements in neuromuscular factors (i.e. upper leg muscle strength and knee proprioception) underlie the beneficial effects of exercise therapy in patients with knee OA. Design: Secondary analyses from a randomised controlled trial, with measurements at baseline, 6 weeks, 12 weeks and 38 weeks. Setting: Rehabilitation centre. Participants: One hundred and fifty-nine patients diagnosed with knee OA. Intervention: Exercise therapy. Main outcome measures: Changes in pain [numeric rating scale (NRS)] and activity limitations [Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) physical function subscale and get-up-and-go test] during the study period. Independent variables were changes in upper leg muscle strength and knee joint proprioception (i.e. motion sense) during the study period. Longitudinal regression analyses (generalised estimating equation) were performed to analyse associations between changes in upper leg muscle strength and knee proprioception with changes in pain and activity limitations. Results: Improved muscle strength was significantly associated with reductions in NRS pain B coefficient −2.5 [95% confidence interval (CI) −3.7 to −1.4], meaning that every change of 1 unit of strength was linked to a change of −2.5 units of pain, WOMAC physical function (−8.8, 95% CI −13.4 to −4.2) and get-up-and-go test (−1.7, 95% CI −2.4 to −1.0). Improved proprioception was not significantly associated with better outcomes of exercise therapy ( P > 0.05). Conclusions: Upper leg muscle strengthening is one of the mechanisms underlying the beneficial effects of exercise therapy in patients with knee OA.